Information system to support the operation of the car park - Kaplanović, Nemanja D. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Information systems represent a set of people, data, processes and information technologies related to the purpose of data collection, processing, storage and their filtering into useful information needed for supporting organizations or decision making. The information system is developed as a Web application with the help of the Javascript programming language, Node.js, and React.js, while in the background it relies on data storage and communication with the SQL database.Methods: Modern web application development tools are used and tested on low budget hardware.Results: Effective software for a car park with low maintenance cost and great reliability has been developed.Conclusion: The software made work easier, increased access to data and facilitated data review, reducing the possibility of error. The application described in this article and made for research shows how modern commercial technologies can be used for military purposes.
Keywords: software; solution; car park; JavaScript; node; SQL; military; technology